THE ROLE OF CONFLICTS ON TEAMWORK EFFECTIVENESS: A STUDY OF THAI AND GERMAN EMPLOYEES OF AN INTERNATIONAL AIRLINE - Peratanasumran, Supaporn (PEOPLE: International Journal of Social Sciences, 2017)
Conflicts seemed to be an everyday phenomenon in each organization. Nowadays, many multiethnic organizations realize how importance of conflict on teamwork effectiveness. This study anticipates not only examining how conflicts have an effect on teamwork performance, but also to investigate how flight attendants resolve interpersonal conflicts. Moreover, to suggest an appropriate approach to overcome conflict encountered. Nevertheless, the main objective is not to eliminate it but to learn how to manage it productively. The study adopts in-depth interview approach of qualitative investigation for data collection. Respondents are Thai, and German flight attendants of an international Airline who reported experiencing in conflict with their colleagues in the past two years and the strategy they adopted to manage such conflicts from their own perspectives. The result of the study indicated that the main cause that initiated conflicts for Thai flight attendants is discrimination; whereas German flight attendants mentioned the two major factors that cause conflicts which are lack of communication and misinterpretation. Surprisingly that conflict management styles both of them used is competing. However, both Thai and German strongly agreed that conflicts play tremendous role on teamwork performance. They believed that it is people who initiate and engage in conflict and determine whether it will finally be productive or destructive. Nevertheless, his study provided some suggestions to de-escalate conflicts that respondents experienced as it is the main goal of its solution.